Mekanisme Kognitif Niat Beli Produk Kosmetik Halal: Peran Mediasi Halal Awareness pada Pengaruh Religious Belief dan Sertifikasi Halal - Shahrul Rossi; Amelindha Vania (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to examine the effect of religious belief and halal certification on purchase intention of Safi halal cosmetic products, with halal awareness as a mediating variable. A quantitative approach was employed using a survey method involving 170 potential consumers in Malang City who were aware of Safi products but had never made a purchase. The data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS 3 software. The results indicate that religious belief and halal certification have a positive and significant effect on halal awareness and purchase intention. Furthermore, halal awareness is proven to have a positive and significant influence on purchase intention and partially mediates the relationship between religious belief and halal certification on purchase intention. These findings suggest that stronger religious values and clear halal certification enhance consumers’ halal awareness, which subsequently increases their intention to purchase halal cosmetic products.